Active in community service programmes, Muhammad Syafiq receives Sapura Industrial Excellence Award - Siti Nurfarmy, Ibrahim (UMPSA, 2024)
GAMBANG, 27 October 2024 – Muhammad Syafiq Mohd Wahidan, 24, the son of a retired military officer, Mohd Wahidan Amat Karim, 50, and a teacher, Aizamiah Ahmad, 48, was named the recipient of the Sapura Industrial Excellence Award at the 19th Convocation Ceremony of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), held at the UMPSA Sports Complex Hall, Gambang Campus.